Intellectual Capital Dan Kinerja Keuangan Perusahaan Manufaktur High Ic Intensive - Hermawan, Sigit; Mardiyanti, Ummy Imaniar (Universitas Muhammadiyah Surakarta, 2016)
This study aims to examine and analyse the effect of intellectual capital on firm financial performance (ROA, ROE, EPS). The company studied is the manufacturing High IC Intensive companies listed in Indonesia Stock Exchange. sample obtained with as many as 76 companies with research period is 2010-2013. Independent variables used are the intellectual capital measured using VAICTM, while the dependent variable is Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS). The data analysis technique used is a simple linear regression. The results showed that the Intellectual Capital (VAIC) effect the companys financial performance Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS).